Effect of Macroeconomic Variables On Stock Price in Nepal - Khatri, Shyam Kaji; Sharma, Bhanu Bhakta; Shrestha, Sharan; Thapa, Dharma Jung (Bagiswori Journal, 2026)
This study explores how variations in major macroeconomic indicators affect stock market performance in Nepalese stock market. This study examines how macroeconomic factors, such as inflation rate, exchange rate and market capitalization, affect the price of shares in Nepal. Secondary time-series data from FY 2000 to FY 2024 were used in the analysis. This study analyzed descriptive statistics, correlation analysis, multiple regression analysis, ANOVA, and beta analysis. The findings provide evidence that the major variable affecting stock price is market capitalization. The findings offer important insights policymakers, investors, and for future research into the Nepalese financial market.